El papel de los "fundamentals" macroeconómicos en las crisis financieras: el caso argentino - Lanteri, Luis (1999)
The turmoils occurred in East Asia in the 1990s have reminded the world of how rapidly and with what disruptive forte financial crises can erupt, and of how diflicult it is to foresee the timing and full ramitications of these dramatic events.In this way, the paper examines the financial system distress and crises in Argentina between 1977 and 1998 (post-Financial Reform period). The paper uses a vector error correction model developed by Johansen and the empirical results identify several adverse macroeconomic shocks that may explain financial crises.We find that financial crises tend to emerge with the following: a fallin real GDP growth, credit expansion, capital outflows, rising M2/intemational reserves ratio, a decline in the real exchange rate and adverse trade shocks. The paper also shows that a weak macroeconomic environment (low GDP growth) is significant in predicting financial crises.The paper concludes that to better manage crises, policymakers should develop a regulatory framework that allows banks to respond more robustly to adverse macroeconomic shocks.